Legal Protection of Military Medical Personnel in Disaster Area Assignments Under Law Number 17 of 2023 on Health - Putri, Dyah Selvia; Sutarno , Sutarno; Pramono, Budi (Devotion : Journal of Research and Community Service, 2025)
In carrying out duties in disaster areas, various factors affect the rescue actions of military medical personnel assisting victims. The government and relevant agencies must ensure legal protection for these personnel in performing their professional duties. This study examines the form of legal protection for military medical and health personnel assigned to disaster areas under the enactment of Law Number 17 of 2023 on Health, focusing on both criminal and civil law. Using a normative juridical approach, the analysis explores the application of relevant laws and the conceptual understanding of legal principles related to military medical practice. The findings show that military medical personnel must possess STR and SIP and are entitled to legal protection, as medical risks may arise even when procedures comply with established SOPs. If disputes occur in criminal or civil matters, patients may file complaints with the MDP. Subsequent proceedings include an examination, a public hearing, and recommendations by the MDP to the concerned personnel. Should any personnel be found at fault, they remain entitled to redress through both military and general judiciary channels, provided their actions adhered to professional service standards and that initial resolution efforts are pursued through alternative dispute mechanisms outside the court.